DIGITAL SCIENCE TEACHING MATERIALS INTEGRATED WITH SCAFFOLDING PROBLEM-BASED LEARNING FOR PROBLEM-SOLVING AND SCIENTIFIC REASONING SKILLS OF PROSPECTIVE MADRASAH IBTIDAIYAH TEACHERS ON KINEMATICS MATERIAL - Rizki Amelia; Ahmad Abtokhi (Jurnal Cakrawala Pendas, 2023)
The ability to solve problems and reason scientifically is needed by prospective elementary schools or Madrasah Ibtidaiyah teachers to meet the demands of the 21st century. This study aimed to determine the effect of digital science teaching materials based on scaffolding problem-based learning on students' scientific thinking skills and problem-solving. This research is quasi-experimental quantitative research with a pre-test-post-control group design. The sample of this study was 24 PGMI students at UIN Maulana Malik Ibrahim Malang who chose the concentration of Natural Sciences. The research instrument used scientific reasoning tests and problem-solving, which consisted of five descriptive questions. Data analysis was performed using paired sample t-test. Data analysis showed that students who used scaffolding problem-based learning digital science teaching materials had higher scientific thinking and problem-solving skills than those who did not use these materials. Therefore, it can be concluded that digital science material influences students' scientific thinking skills and problem-solving. Kemampuan memecahkan masalah dan bernalar secara ilmiah sangat dibutuhkan calon guru sekolah dasar atau Madrasah Ibtidaiyah untuk memenuhi tuntutan abad 21. Tujuan pelaksanaan riset berikut guna memberi pendeskripsian pengaruhnya bahan ajar sains digital berbasiskan scaffolding problem-based learning terhadap kemampuan berpikir ilmiah dan pemecahan permasalahan mahasiswa. Riset berikut ialah riset kuantitatif dengan desain kuasi eksperimen pre-post-control group design. Sampel penelitian ini adalah 24 mahasiswa PGMI UIN Maulana Malik Ibrahim Malang yang memilih konsentrasi Ilmu Pengetahuan Alam. Instrumen penelitian ini menggunakan tes penalaran ilmiah dan pemecahan masalah yang terdiri dari lima pertanyaan deskriptif. Analisis data dilakukan dengan menggunakan uji-t sampel berpasangan. Analisis data menandakan yakni murid yang mempergunakan bahan ajar digital sains berbasis scaffolding PBL memiliki tingkat berpikir ilmiah dan keterampilan pemecahan masalah yang lebih tinggi daripada siswa yang tidak menggunakan bahan tersebut. maka begitu, berkeismpulan yakni bahan ajar sains digital berbasiskan scaffolding PBL membawa pengaruh kepada keterampilan berpikir ilmiah dan pemecahan masalah siswa.